Analysis of Hero’s Journey in Jack London’s "The Call of The Wild" - Julius; Satria, Robby (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This research has the purpose to identify the stages of hero’s journey in Jack London’s novel entitled “The Call of the Wild”, experienced by the main character as the hero. “The Call of the Wild” is a novel that has heroic aspect as the story develops. This novel talks about adventure of a dog that went from a domesticated life into a wild beast. The dog went through sequence of event which then led him to a noble ending. Hero’s journey is a sequence of heroism where experience have distinct characteristic, in which Campbell (2008)mentioned that the pattern is prominent in heroic fiction referred as monomyth. This research applied the design of descriptive qualitative in order to explore detail process of the analysis. The used method to collect data is by using the method of library research by Ratna (2004), and the data analysis used the method of descriptive analysis by Ratna (2004). The result of the research has showed that Buck, the main character of the novel has gone through three stages of hero’s journey with the eight steps of it, they are four steps out of five in departure stage, three steps out of six in initiation stage, and one step out of six in return stage. This leads to the conclusion of hero’s journey is often following the same pattern as theorized and mentioned in the theory of Joseph Campbell.